The Influence of Information Technology Utilization and Work Effectiveness on Work Culture with Competence as a Variable Intervening at the Medan Religious Education and Training Center - Itrawati, Itrawati; B, Mesra (CV. Lafadz Jaya, 2023)
Based on this research, researchers want to see the influence of the use of information technology and work effectiveness on work culture with competency as an intervening variable. This type of research is quantitative research with the research location being at the Medan Religious Education and Training Center office. The entire population was sampled, totaling 60 employees. The results of this research are that work effectiveness has a positive and significant effect on work culture. Work effectiveness has a positive and significant effect on competence. Competency has a positive and significant effect on work culture. The use of Information Technologyhas a positive and significant effect on Competency. The use of Information Technology has a positive and significant effect on Work Culture. Work effectiveness has a positive and significant effect on work culture through competence. The use of information technology has a positive and significant effect on work culture through competence at the Medan Religious Education and Training office.